Evaluasi Kebijakan Partisipasi Anak Melalui Forum Anak Oleh Dinas Pemberdayaan Perempuan Perlindungan Anak dan Pemberdayaan Masyarakat Kota Tanjungpinang - Indri Lestari (Jurnal Riset Multidisiplin Edukasi, 2025)
Children are an important element in the sustainability of a nation, state, and humanity. As the next generation with great potential, children play a strategic role in the development of the nation's future. Therefore, it is important to provide them with ample opportunities to grow and develop physically, mentally, socially, and morally. Protection and support for children is a shared responsibility of the state, government, society, family, and parents. In an effort to protect children's rights, Indonesia regulates child protection in various regulations, including Law Number 23 of 2002 which has been amended to Law Number 35 of 2014. One form of implementation of this regulation is the establishment of the Children's Forum, as a forum for children's participation in the decision-making process. This study analyzes the effectiveness of the Tanjungpinang City Children's Forum using William Dunn's policy evaluation theory, which includes six indicators: effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The results of the study indicate that the Tanjungpinang City Children's Forum has played an important role in increasing children's participation, although there are still challenges related to access to information and the involvement of children from various backgrounds. In addition, the implementation mechanism of the Children's Forum has been running well, although there is some room to improve the responsiveness and suitability of policies to the needs of children in the city.